Comparison Between Impulsive and Periodic Non-Newtonian Lubrication of Human Hip Joint - K.Ch. WIERZCHOLSKI (Engineering Transactions)
This paper shows numerical comparisons between lubrication of human hip joint gap in unsteady impulsive and periodic motion. We assume that spherical bone head in human hip joint moves at least in two directions namely in circumference and meridian directions. Basic equations describing synovial fluid flow in human hip joint are solved on the analytical and numerical way. Numerical calculations are performed in Mathcad 11 Professional Program, taking into account the method of Finite Differences. This method satisfies stability of numerical solutions of partial differential equations and gives real values of pressure and capacity forces occurring in human hip joints.